Penyusunan Anggaran Operasional Sebagai Fungsi Manajemen pada Depot Karya Jaya Palembang - Shabrina Tyas Permata; Markoni Badri; Marieska Lupikawaty (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This research explained about the preparation of an operational budget as a management function at Depot Karya Jaya. This study uses secondary data in the form of sales data in the last five years. The analysis technique used in this research was quantitative method in the form of budget calculations related to the company operational activities. Data collection techniques were carried out by means of interviews and library research. The results showed that the preparation of an operational budget not only requires of sales data in the previeous year, but also requires sales targets and policies that related to the company operational activities. In management function, budget can be used as a planning function which can be used as a guideline for achieving the targets of company. As a controlling function, the budget that has been prepared needs to be reviewed periodically so if the company’s condition is not same with the planned budget, the company can adjust the budget according to the conditons that happen nowdays